Central Insulin Sensitivity in Male and Female Juvenile Rats - Keen-Rhinehart, Erin (2009)
The incidence of juvenile obesity is increasing at an alarming rate. In adults, central insulin administration decreases hypothalamic orexigenic neuropeptides, food intake and body weight more effectively in males than females. Mechanisms regulating energy balance in juvenile animals are inherently different from those in adults due to differences in growth rates and hormonal milieu. Therefore, we sought to determine if central insulin treatment in juvenile rats (4 wk) would have similar sex-dependent effects on food intake as those reported in adult rats. Twenty four hour food intake was measured following icv saline or insulin (0.01 or 0.1 U) prior to the onset of dark phase of the light cycle. An additional set of animals was used to assess the effects of central insulin on hypothalamic orexigenic (NPY, AgRP) and anorexigenic (POMC) neuropeptide mRNA expression. In both males and females, insulin reduced meal size initially (first 4h) and later decreased meal frequency (4–24 h) to reduce cumulative food intake. Consistent with this, central insulin decreased hypothalamic NPY and AgRP and increased POMC mRNA expression. In contrast to adult studies, there were no demonstrated sex differences. These studies indicate that juvenile females and males are equally sensitive to central insulin anorexigenic effects, perhaps due to a lack of circulating gonadal hormones. The anorexigenic responsiveness of both genders suggests a potential pharmacologic approach to childhood obesity.